2013
DOI: 10.1371/journal.pone.0066241
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal MEG Oscillatory Activity during Visual Processing in the Prefrontal Cortices and Frontal Eye-Fields of the Aging HIV Brain

Abstract: ObjectiveShortly after infection, HIV enters the brain and causes widespread inflammation and neuronal damage, which ultimately leads to neuropsychological impairments. Despite a large body of neuroscience and imaging studies, the pathophysiology of these HIV-associated neurocognitive disorders (HAND) remains unresolved. Previous neuroimaging studies have shown greater activation in HIV-infected patients during strenuous tasks in frontal and parietal cortices, and less activation in the primary sensory cortice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…This implicates HIV in injury to multimodal association regions of the brain, which is also suggested by abnormal levels of brain activation in the dorsolateral prefrontal (DLPFC) and parietal cortices in HIV positive participants compared to healthy controls during the performance of working memory, attention, risky decision-making, and executive functioning tasks (Chang et al, 2001; Chang et al, 2004; Connolly et al, 2014; Ernst, Chang, Jovicich, Ames, & Arnold, 2002; Melrose, Tinaz, Castelo, Courtney, & Stern, 2008). Similar disruptions in local magnetic field potentials within the lateral PFC have been reported in HIV patients using magnetoencephalography (MEG), both at rest (Becker et al, 2012) and during the performance of visual attention (Wilson, Fox, et al, 2013) and fine motor control (Wilson, Heinrichs-Graham, et al, 2013) tasks.…”
Section: Introductionsupporting
confidence: 68%
“…This implicates HIV in injury to multimodal association regions of the brain, which is also suggested by abnormal levels of brain activation in the dorsolateral prefrontal (DLPFC) and parietal cortices in HIV positive participants compared to healthy controls during the performance of working memory, attention, risky decision-making, and executive functioning tasks (Chang et al, 2001; Chang et al, 2004; Connolly et al, 2014; Ernst, Chang, Jovicich, Ames, & Arnold, 2002; Melrose, Tinaz, Castelo, Courtney, & Stern, 2008). Similar disruptions in local magnetic field potentials within the lateral PFC have been reported in HIV patients using magnetoencephalography (MEG), both at rest (Becker et al, 2012) and during the performance of visual attention (Wilson, Fox, et al, 2013) and fine motor control (Wilson, Heinrichs-Graham, et al, 2013) tasks.…”
Section: Introductionsupporting
confidence: 68%
“…In the current study, we observed a disease-related reduction in gamma power in response to electrical stimulation. Previous studies using neuroimaging modalities such as fMRI and MEG have provided evidence for similar disease-related alterations in the primary visual, motor and somatosensory cortices ( Ances et al, 2009 ; Ances et al, 2010 ; Wilson et al, 2013a ; Wilson et al, 2015 ; Wilson et al, 2013b ). Specifically, using fMRI, Ances and colleagues found reduced activity in the primary visual cortices during visual stimulation and at rest in HIV-infected adults ( Ances et al, 2009 ; Ances et al, 2010 ).…”
Section: Discussionmentioning
confidence: 84%
“…Previous neuroimaging studies investigating the impact of HIV infection on cognitive and sensory processing suggest hyperactivation in frontal and parietal regions during cognitive tasks, and hypoactivation in primary visual cortices during visual tasks and at rest ( Ances et al, 2011 ; Ances et al, 2009 ; Ances et al, 2010 ; Chang et al, 2004 ; Chang et al, 2008 ; Ernst et al, 2002 ; Wiesman et al, 2018 ; Wilson et al, 2013a ; Wilson et al, 2017 ). For example, a study of resting cerebral blood flow (rCBF) revealed diminished rCBF within the lenticular nuclei and visual cortex for HIV-infected participants compared to uninfected controls.…”
Section: Introductionmentioning
confidence: 98%
“…Visuospatial dysfunction in HIV-infected participants has been well documented; however, the underlying neurophysiology of these impairments has remained elusive until fairly recently. [2][3][4]10,33 In addition to these functional imaging studies, the visual cortices have been found to be preferentially vulnerable to HIV-related degeneration, 34 an effect which may be due to latent viral reservoirs instigating immune system decline in these regions. 34,35 Despite these advances, the role of aging in these visuospatial deficits has not been examined, which is surprising because these same cognitive faculties degrade substantially as a function of age in uninfected populations.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-associated neurocognitive disorders (HAND) are a persistent concern for those living with HIV and include substantial impairments to visuospatial processing. [1][2][3][4] A greater understanding of the neural dynamics underlying these impairments has the potential to enhance diagnosis of HAND and inform prognoses and further delineation of HAND subtypes. Previous structural and functional imaging research has reported neural aberrations in visual-perceptual networks in HIV-infected adults.…”
mentioning
confidence: 99%